2009
DOI: 10.2353/ajpath.2009.080463
|View full text |Cite
|
Sign up to set email alerts
|

Expression of CD74, the Receptor for Macrophage Migration Inhibitory Factor, in Non-Small Cell Lung Cancer

Abstract: Macrophage migration inhibitory factor (MIF) is a multifunctional cytokine that is overexpressed in lung cancer. The MIF receptor was recently discovered and found to be the invariant chain of the HLA class II molecule, CD74. We hypothesized that the expression of this receptor-ligand pair in lung cancer is associated with the angiogenic activity and level of CXC chemokine expression in human specimens of non-small cell lung cancer. We, therefore, performed immunolocalization of CD74 and compared it with the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
59
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 84 publications
(70 citation statements)
references
References 44 publications
4
59
0
4
Order By: Relevance
“…Furthermore, our data confirmed worst prognosis for high-grade glioblastoma with high levels of CD74 expression. However, our data suggest that CD74 expression alone is not an independent marker for poor prognosis and it requires the expression of MIF for tumor pathogenesis, as previously reported in other studies (4,7,16,17,18) . Although we did not perform co-localization staining for MIF-CD74 in this retrospective study, evidence of MIF and CD74 co-localization reported in several other studies (7,8,9,10,11,12,13,14) .…”
Section: Discussionsupporting
confidence: 63%
See 4 more Smart Citations
“…Furthermore, our data confirmed worst prognosis for high-grade glioblastoma with high levels of CD74 expression. However, our data suggest that CD74 expression alone is not an independent marker for poor prognosis and it requires the expression of MIF for tumor pathogenesis, as previously reported in other studies (4,7,16,17,18) . Although we did not perform co-localization staining for MIF-CD74 in this retrospective study, evidence of MIF and CD74 co-localization reported in several other studies (7,8,9,10,11,12,13,14) .…”
Section: Discussionsupporting
confidence: 63%
“…Postoperative KPS scores have superior predictive capabilities for overall survival in glioblastoma patients and should replace preoperative KPS scores when estimating prognosis (20) . Similar to previous association studies of CD74 expression and survival in other cancers, KaplanMeier overall survival analyses for CD74 expression levels revealed a significant association between high CD74 expression and poorer prognosis (log-rank test, P = 0.05) (7,10,11) . Furthermore, our data confirmed worst prognosis for high-grade glioblastoma with high levels of CD74 expression.…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations